El cambio semántico de los homónimos piola1 y piola2: origen latino y lunfardo - Vicente Zegarra, Ana Krista (2022)
This article focuses on the semantic change that the homonyms piola1 and piola2 have undergone, from their origin with the Latin word pediŏla 'traba', which can refer to a 'rope' as well as to a game quite popular in Spain, to the colloquial lunfardo language of Argentine origin piolín ('piola'), which passes into current Spanish with the meanings of 'astute', 'nice', 'great', 'skillful', 'quiet', 'discreet' and 'unnoticed'. This article seeks to make contributions in the field of semantics; likewise, the general objective is to explain the semantic change of piola1 and piola2 brought about through the cognitive mechanisms of metaphor and metonymy. The theoretical framework used is the one provided by cognitive semantics where the theory of prototypes, categorization, metaphor and metonymy are found. Likewise, the semantic changes that were adopted in different countries of South America and Spain during the 19th, 20th and 21st centuries are shown; the information was collected from the main databases of the RAE: CORDE, CREA and CORPES. Finally, radial diagrams are presented in order to show a greater elucidation of the two origins with the respective meanings of piola.